Caleb's crossing [large type] : a novel - Brooks, Geraldine (Thorndike Press large print core, 2011)
Growing up in the tiny settlement of Great Harbor amid a small band of pioneers and Puritans, Bethia Mayfield yearns for an education that is closed to her due to her gender. As soon as she can, she slips away to explore the island's glistening beaches and observes its native Wampanoag inhabitants. At twelve, she encounters Caleb, the young son of a chieftain, and the two forge a secret friendship that draws each into the alien world of the other.